Influence of integrated nutrient management and biofertilizer on growth, yield and soil fertility of Blond psyllium (Plantago ovata) cultivation under semi-arid conditions - Shivran, A. C.; Choudhary, I.; Puniya, M. M. (Annals of Agricultural Research, 2016)
A field experiment consisting of eighteen treatment combinations with six treatments of fertilizers/ manures (control, RDF [40 kg N + 30 kg P2O5 /ha], FYM 8.0 t/ha, vermicompost 3.0 t/ha, FYM 4.0 t/ha + 50% RDF and vermicompost 1.5 t/ha + 50% RDF) and three biofertilizers (control, Azotobacter and Azospirillum) was conducted using randomized block design with three replications. Fertilizers/ manures application alone or in combination significantly influenced the growth, yield and net returns as compared to control. The significantly higher seed and straw yields were recorded with vermicompost 1.5 t/ha + 50 % RDF over control, RDF, FYM 8.0 t/ha, vermicompost 3.0 t/ha and FYM 4.0 t/ha + 50% RDF. Application of FYM 4.0 t/ha + 50% RDF also recorded significantly higher seed and straw yields over control, RDF alone and FYM 8.0 t/ha, however it was at par to application of vermicompost 3.0 t/ha alone. The harvest index was not affected by application of fertilizers/manures. Vermicompost 1.5 t/ha + 50 % RDF recorded maximum net returns (Rs 31462/ha) which was significantly superior over rest of the treatments except RDF alone. The inoculation with biofertilizers i.e., Azotobacter and Azospirillum significantly increased the seed and straw yields over no inoculation. However, the harvest index remained unaffected. Significantly higher net returns (Rs 26507 /ha) was obtained with Azotobacter inoculation, being at par to Azospirillum, over no inoculation. The fertilizers/manures significantly improved organic carbon and available NPK in soil and highest values were obtained with FYM @ 8.0 t/ha followed by vermicompost @ 3.0 t/ha for organic carbon and available N and vermicompost @ 1.5 t/ha + 50% RDF for available PK. There was marginal improvement in soil fertility with biofertilizers.